Design Strategies toward Advanced MOF‐Derived Electrocatalysts for Energy‐Conversion Reactions. Issue 23 (9th June 2017) - Liu, Jinlong; Zhu, Dongdong; Guo, Chunxian; Vasileff, Anthony; Qiao, Shi‐Zhang
Abstract: The key challenge to developing renewable and clean energy technologies lies in the rational design and synthesis of efficient and earth‐abundant catalysts for a wide variety of electrochemical reactions. This review presents materials design strategies for constructing improved electrocatalysts based on MOF precursors/templates, with special emphasis on component manipulation, morphology control, and structure engineering. Guided by these strategies, recently developed MOF‐derived materials have exhibited remarkable activity, selectivity, and stability for various energy‐conversion processes, manifesting great potential for replacing precious‐metal‐based catalysts in next‐generation energy devices. Existing challenges and opportunities regarding MOF‐derived electrocatalysts are also discussed. It is anticipated that by extending current materials design strategies to a wider range of MOF precursors for various energy‐related electrocatalytic reactions, significant advances toward achieving highly efficient electrocatalysts can be made. Abstract : Metal–organic framework (MOF)‐derived materials have stimulated wide‐ranging interest as appealing electrocatalysts for various energy‐conversion reactions. Design strategies, especially component manipulation, morphology control, and structure engineering, are highlighted as important factors for constructing advanced electrocatalysts based on abundant and versatile MOFs, enabling highly improved catalytic properties for next‐generation energy technologies.